Analisis Pengaruh Kualitas Pelayanan Lokasi Dan Harga Terhadap Keputusan Pembelian Pada Toko Prima Elektronik Kalabahi Kabupaten Alor (Studi Kasus Pada Toko Prima Elektronik Kalabahi Kabupaten Alor) - Tuati, Ince Nurida; Maruli, Elia; Awang, Mesak Y.; Anigomang, Ferdinand Romelus (Peneliti.net, 2023)
Ince Nurida Tuati (2023) thesis title analysis of the influence of service quality, location and price on purchasing decisions at the Kalabahi Electronic Prima Store, Alor Regency. This study aims to determine the influence of waiter quality, location and price on purchasing decisions at the Kalabahi Electronic Prima Store, Alor Regency. This type of research is quantitative with data collection techniques are observation, interviews, questionnaires and documentation studies. The sampling technique in this study was accidental sampling with a sample of 40 resonant people. The statistical method in this study is multiple linear analysis and to measure each variable using the t test (partial) and to measure all variables using the F test (simultaneous) using the SPSS 25 For Windows program tool. The results in this study show that (1) partially the service quality variable has a significant value of 0.000 or 0% where this value is smaller than the alpha value of 0.05 or 5%. So that the results in this study received H1 which stated that service quality variables affect purchasing decisions at the Kalabahi Electronic Prima Store, Alor Regency. (2) partially the location variable has a significant value of 0.018 or 1.8% where this value is smaller than the alpha value of 0.05 or 5%. So that the results in this study received H2 which stated that location variables affect purchasing decisions at the Kalabahi Electronic Prima Store, Alor Regency. (3) partially the price variable has a significant value of 0.000 or 0% where this value is smaller than the alpha value of 0.05 or 5%. So that the results in this study received H3 which stated that price variables affect purchasing decisions at the Kalabahi Prima Electronic Store, Alor Regency. (4) simultaneously the variables of service quality, location and price have a significant value of 0.000 or 0% where this value is smaller than the alpha value of 0.05 or 5%. So that the results in this study received H4 which stated that the variables of service quality, location and price affect purchasing decisions at the Kalabahi Electronic Prima Store, Alor Regency.